If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 10 + x + x = 13 + x Reorder the terms: 10 + x + x + x = 13 + x Combine like terms: x + x = 2x 10 + 2x + x = 13 + x Combine like terms: 2x + x = 3x 10 + 3x = 13 + x Solving 10 + 3x = 13 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 10 + 3x + -1x = 13 + x + -1x Combine like terms: 3x + -1x = 2x 10 + 2x = 13 + x + -1x Combine like terms: x + -1x = 0 10 + 2x = 13 + 0 10 + 2x = 13 Add '-10' to each side of the equation. 10 + -10 + 2x = 13 + -10 Combine like terms: 10 + -10 = 0 0 + 2x = 13 + -10 2x = 13 + -10 Combine like terms: 13 + -10 = 3 2x = 3 Divide each side by '2'. x = 1.5 Simplifying x = 1.5
| p=2(6)+2(4) | | 6-3x=-37 | | 5p/7-8=-43 | | 3(-4+x)=4x+(1/3) | | 2t+10-5= | | 9a-6=3a+3a+4+4a | | 3x+2+4y+2+3y= | | 9/7=11/8x+3 | | -7x=-5x-10 | | 4x+7-3x+6= | | 4(34+9x)+16x=32 | | 5x+2(3x-7)=-20+11x+6 | | 10x+x= | | -12b+6b-4b= | | 3/4=x/4 | | 9(16x+4y)+34=32 | | 25m^2-25= | | t=13+x | | 9+2/5=29-11/7 | | 2/-5=6/t | | 3+3x=-6+2x | | t^6-36= | | 1.5x-2.6=3.4 | | 62d-1+13=19 | | x+2x-12+x=-3+2x | | C+1/c-2=4/6 | | (5-x)(2x+3)(x+6)=0 | | 9+2.7t=-4.8t-8 | | 27-x=18.9 | | 9x+81=4x-24 | | 200=5x+55+5x+45 | | 3/4x=6/8 |